A pH- and ionic strength-dependent conformational change in the neck region regulates DNGR-1 function in dendritic cells - Hanc,P; Schulz,O; Fischbach,H; Martin,SR; Kjaer,S; Reis,e Sousa C (EMBO Journal, 2016)
DNGR1 is receptor expressed by certain dendritic cell (DC) subsets and by DC precursors in mouse. It possesses a Ctype lectinlike domain (CTLD) followed by a poorly characterized neck region coupled to a transmembrane region and short intracellular tail. The CTLD of DNGR1 binds Factin exposed by dead cell corpses and causes the receptor to signal and potentiate crosspresentation of dead cellassociated antigens by DCs. Here, we describe a conformational change that occurs in the neck region of DNGR1 in a pH and ionic strengthdependent manner and that controls crosspresentation of dead cellassociated antigens. We identify residues in the neck region that, when mutated, lock DNGR1 in one of the two conformational states to potentiate crosspresentation. In contrast, we show that chimeric proteins in which the neck region of DNGR1 is replaced by that of unrelated Ctype lectin receptors fail to promote crosspresentation. Our results suggest that the neck region of DNGR1 is an integral receptor component that senses receptor progression through the endocytic pathway and has evolved to maximize extraction of antigens from cell corpses, coupling DNGR1 function to its cellular localization.